2004
DOI: 10.1128/iai.72.10.6087-6094.2004
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Airway Inflammation by Immunostimulatory CpG Oligodeoxynucleotides in a Murine Model of Allergic Aspergillosis

Abstract: Allergic aspergillosis is a Th2 T-lymphocyte-mediated pulmonary complication in patients with atopic asthma and cystic fibrosis. Therefore, any therapeutic strategy that selectively inhibits Th2 T-cell activation may be useful in downregulating allergic lung inflammation in asthma. In the present study, we developed a CpG oligodeoxynucleotide (ODN)-based immune intervention of allergic inflammation in a mouse model of allergic aspergillosis. Four different groups of mice were used in a short-term immunization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 21 publications
1
35
0
Order By: Relevance
“…The ability of CpG ODN to trigger the production of T-helper 1 and proinflammatory cytokines and IFN-dependent IgG2a antibodies has been observed with a variety of co-administered antigens [50][51][52][53]. This adjuvant effect was clearly dose dependent and mediated by cytokines produced following stimulation of APC, as for example, IL-12.…”
Section: Discussionmentioning
confidence: 86%
“…The ability of CpG ODN to trigger the production of T-helper 1 and proinflammatory cytokines and IFN-dependent IgG2a antibodies has been observed with a variety of co-administered antigens [50][51][52][53]. This adjuvant effect was clearly dose dependent and mediated by cytokines produced following stimulation of APC, as for example, IL-12.…”
Section: Discussionmentioning
confidence: 86%
“…Although numerous reported epidemiological and experimental studies have demonstrated the inhibitory role of live or killed microbes or microbial components on allergic responses [18][19][20][21][22][23][24][25], the basis for this inhibition remains unclear. In particular, little experimental study has been performed on the effect and mechanism of neonatal microbial exposure on airway allergic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…After 24 h, the cells were stained with allophycocyanin-conjugated anti-CCR3 Ab. Cytospins were prepared from some cultures and stained in the presence of potassium cyanide for eosinophil peroxidase (EPO; exclusive to eosinophils), according to a protocol published previously (36), or with H&E.…”
Section: Cd117mentioning
confidence: 99%